Effect of Coconut Shell-Based Active Carbon Adsorbent on Motorcycle Exhaust Gas Emissions - Putra Gitama, Nahindi; Hidayat, Najmul; Pebrianti, Dwi (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
This study focused on the utilization of active carbon derived from coconut shells as an adsorbent to reduce exhaust gas emissions in motorcycles. The research aimed to compare the exhaust emissions before and after installing active carbon in the muffler and to analyze its effect on the levels of CO, HC, and CO2 at different engine speeds. A laboratory experiment was conducted with varying masses of active carbon, and emission data were collected and analyzed using two-way ANOVA. The results demonstrated that with the use of 200 grams of active carbon, the CO emission decreased by 12.06%, HC by 16.96%, and CO2 by 9.17%. These reductions are attributed to the strong adsorptive properties of active carbon, which facilitated the physical and chemical separation of harmful gases. The study concluded that active carbon significantly reduces exhaust emissions, providing a practical solution for improving air quality in motorcycles. The findings offer an effective method for emission control that could be applied under various operating conditions, making it suitable for widespread implementation in emission-reduction systems for small engines.